DNA Methylation Level of Transcription Factor Binding Site in the Promoter Region of Acyl-CoA Synthetase Family Member 3 (ACSF3) in Saudi Autistic Children [Corrigendum] - Algothmi K; Alqurashi A; Alrofaidi A; Alharbi M; Farsi R; Alburae N; Ganash M; Azhari S; Basingab F; Almuhammadi A; Alqosaibi A; Alkhatabi H; et al. (Dove Medical Press, 2023)
Algothmi K, Alqurashi A, Alrofaidi A, et al. Pharmgenomics Pers Med. 2022;15:131–142. The authors have advised affiliation 4 on page 131 is incorrect. The correct affiliation should read “Medical Laboratory Technology Department, Faculty of Applied Medical Sciences, King Abdulaziz University, Jeddah, Saudi Arabia”. The authors apologize for this error.